Carcinoma de pequenas células do esôfago - Souza,Hamilton Petry de (1998)
Small cell carcinoma of the esophagus is a rare tumor described to the first time by Mckeown in 1952. Clinically it is very similar to small cell carcinoma of the lung. with quick evolution and early dissemination.It is more frequent in men between 60 and 70 years of age. The patients usually have dysphagia and weight loss. Most of the tumours arise in the middle and distal third of the esophagus. Chronic alcohol and tobacco use are usually present. The manegement of primary small cell cancer of the esophagus remains controversial with groups reporting treatment based on operation alone, local radiotherapy, chemotherapyalone, or operation with adjuvant therapy. Overall survivel remains poor at a mean of 5.1 months, with the best rate of survivel in patients undergoing operation with adjuvant chemotherapy. The authors relate two cases of a small cell carcinoma of the esophagus. Both of these patients was female and white, with 51 and 64 years old. The first mainestation was dysphagia and weight loss. Histologic study from endoscopic biopsies reveled the diagnosis. The treatment was, in the both cases surgery, however in one case, chemotherapy and mediastinal irradiation was associated to the ressection. The authors comment the more important aspects about this pathology and the treatment and survival of the patients.